Development of extraction and analysis of protocols for RNA in formalin-fixed paraffin-embedded (FFPE) materials using TaqMan® real-time PCR - Li, Jinghuan (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Histopathology & Morbid Anatomy, 2009)
Archival Formalin-Fixed, Paraffin-Embedded (FFPE) tissue samples represent an invaluable source of human tissue for gene expression analysis. They are the most abundant and readily available materials and generally well documented with clinical pathological parameter. Data generated can potentially highlight biomarkers useful in disease classification, diagnosis and prognosis, and elucidate novel therapeutic targets. However, they have not been widely used in molecular biology due to the compromised RNA molecules extracted from these tissues which are degraded and chemically modified. Thus, the value of FFPE materials in molecular setting has been shadowed by the technical difficulties limiting extensive analysis of gene expression. The purpose of this project is to establish a reliable analysis system to study gene expression level using RNA extracted from FFPE materials.
Keywords: Histopathology, Ph.D.; Ph.D. Trinity College Dublin